A production process of environmentally friendly sound-proof composite material

By using biodegradable PE polymer materials and bio-based polyester fibers in silent materials, combined with advanced process and technical means, a silent composite material with excellent silent performance, environmental protection and versatility is prepared, which solves the shortcomings of existing silent materials in terms of environmental performance, durability and functions.

CN118358224BActive Publication Date: 2025-03-18YANCHENG DONGHAI WATER SUPPLY EQUIP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410638254.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-03-18
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The existing silent materials have shortcomings in environmental performance, durability, manufacturing process complexity and single functions, and it is difficult to meet the requirements of environmental protection, efficient vibration reduction and noise reduction, durability, etc. at the same time.

Method used

A variety of environmentally friendly materials such as biodegradable PE polymer materials, bio-based polyester fibers, phase change material microcapsules, nanosilicates and conductive fillers are prepared through technical means such as ultrasonic pretreatment, cross-linking network formation, high-voltage homogeneous dispersion, combined with hot melt bonding technology and rolling alignment technology, an environmentally friendly silent composite material with excellent silent performance is prepared.

Benefits of technology

It realizes the efficient vibration and noise reduction performance of environmentally friendly silent composite materials, improves the durability and versatility of the material, and has good corrosion resistance, aging resistance, temperature resistance and fire resistance, and is suitable for a variety of application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118358224B_ABST
    Figure CN118358224B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of metal-based composite materials, and in particular to a production process of an environmentally friendly sound-proof composite material, comprising the following components: PE polymer material, metal sheet, bio-based polyester fiber, phase change material microcapsule, nano-silicate, conductive filler, cross-linking agent, plasticizer, adhesive. The present invention provides an environmentally friendly, high-performance, multifunctional sound-proof composite material. Biodegradable materials are selected to save energy and reduce emissions, and the composite material has excellent soundproofing, strength, durability, smooth surface, high hardness, good soundproofing effect, and is also anti-corrosion, anti-aging, heat-resistant, and fire-resistant. The surface meets food-grade standards and is widely used, with broad application prospects and significant social and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal-based composite materials, and in particular to a production process of an environmentally friendly sound-proof composite material. Background Art

[0002] With the rapid development of modern industry and the improvement of people's living standards, the requirements for material performance are also increasing. Especially in today's increasingly serious noise pollution, it is particularly important to develop a composite material that is both environmentally friendly and has good quiet performance. Traditional quiet materials often cannot meet the requirements of environmental protection, high-efficiency vibration and noise reduction, durability, etc. Therefore, the research and development of new environmentally friendly quiet composite materials has become a research hotspot in the current field of materials science.

[0003] Existing sound-absorbing composite materials are mostly made of rubber, plastic, glass fiber and other materials. Although these materials have a certain sound-absorbing effect, they also have many problems.

[0004] Insufficient environmental performance: Many traditional sound-absorbing materials, such as rubber and some plastics, may release harmful substances during production and use, causing harm to the environment and human health. At the same time, these materials are often difficult to degrade, bringing long-term burdens to the environment.

[0005] Poor durability: After long-term use, the noise-reducing performance of existing noise-reducing materials often drops significantly due to material aging, wear and tear, etc.

[0006] The manufacturing process is complex and energy-intensive: The manufacturing process of traditional sound-absorbing materials is usually complex and requires a lot of energy, which is contrary to the current environmental protection concept of energy conservation and emission reduction.

[0007] Single function: Existing sound-absorbing materials often only focus on the functions of vibration reduction and noise reduction, while ignoring other multifunctional requirements such as strength, corrosion resistance, anti-static, etc., and the applicable fields are single.

[0008] Therefore, we proposed a production process of an environmentally friendly sound-proof composite material, which can be widely used in drinking water tanks, fire water tanks, chemical storage tanks, underground water pools, swimming pools, breeding pools, indoor and outdoor wall panels, door panels, desktop panels, roofs and other fields. It is energy-saving, environmentally friendly, and does not fade, and is used to solve the above problems. Summary of the invention

[0009] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a production process for an environmentally friendly sound-proof composite material.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] An environmentally friendly soundproof composite material comprises the following components in parts by weight: 10 to 20 parts of PE polymer material, 100 to 150 parts of metal plate, 10 to 15 parts of bio-based polyester fiber, 5 to 10 parts of phase change material microcapsules, 3 to 5 parts of nano silicate, 5 to 10 parts of conductive filler, 1 to 3 parts of crosslinking agent, 2 to 4 parts of plasticizer and 2 to 4 parts of adhesive.

[0012] As the preferred technical solution:

[0013] The environmentally friendly sound-proof composite material as described above includes the following components in parts by weight: 15 parts of PE polymer material, 120 parts of metal sheet, 12 parts of bio-based polyester fiber, 6 parts of phase change material microcapsules, 4 parts of nano-silicate, 7 parts of conductive filler, 2 parts of cross-linking agent, 3 parts of plasticizer, and 3 parts of adhesive.

[0014] In the above-mentioned environmentally friendly soundproof composite material, the PE polymer material is polyethylene, the molecular weight of the PE polymer material is 100,000 to 300,000 Daltons, and the melt index is 1 to 10 g / 10 min at 190°C / 2.16 kg; the metal plate is one or more of aluminum plate, steel plate, and copper plate, the thickness of the metal plate is 0.1 to 0.5 mm, and the surface roughness Ra value is less than 0.8 μm; the bio-based polyester fiber is a bio-based polyester fiber made from corn starch, and the bio-based polyester fiber The fiber diameter is between 10 and 30 μm, and the fiber length is between 3 and 12 mm; the phase change material microcapsule contains phase change material paraffin, the microcapsule diameter of the phase change material microcapsule is between 5 and 50 μm, and the phase change temperature range is between 20 and 30°C; the conductive filler is selected from one or more of carbon black, carbon nanotubes, and graphene, the cross-linking agent is a silane cross-linking agent, the plasticizer is one of an epoxy plasticizer and a citrate plasticizer, and the adhesive is one or more of a plant-based adhesive, a water-based polyurethane adhesive, and a bio-based composite adhesive.

[0015] An environmentally friendly soundproof composite material as described above, wherein the polymer chain of the PE polymer material has n+1 branch structures, the length of each branch structure is 1 / 3 to 1 / 2 of the length of the main chain, and / or the polymer chain has multiple cross-linking points;

[0016] Assuming the ratio of the length of the branch structure to the length of the main chain is R_{branch}, then:

[0017] R_{branch}=\frac{L_{branch}}{L_{main}}

[0018] Among them, L_{branch} is the average length of the branch structure; L_{main} is the length of the main chain; it is used to ensure that the length of the branch structure is 1 / 3 to 1 / 2 of the length of the main chain;

[0019] Assuming the complexity of the branch structure is C_{branch}, then:

[0020] C_{branch}=\frac{N_{branches}}{N_{levels}}

[0021] Where, N_{branches}: the total number of branches; N_{levels}: the level of the branch structure; this complexity index evaluates the impact of the branch structure on material properties;

[0022] Assuming the density of crosslink points is D_{crosslink}, then:

[0023] D_{crosslink}=\frac{N_{crosslink}}{L_{chain}}

[0024] Wherein, N_{crosslink}: the number of crosslink points on the polymer chain; L_{chain}: the total length of the polymer chain, including the main chain and branch chains; the crosslink point density reflects the degree of crosslinking of the polymer chain;

[0025] The shell of the phase change material microcapsule undergoes reversible deformation when the temperature changes, presenting a tightly arranged linear structure at low temperatures and changing into a loose network structure at high temperatures, thereby achieving more efficient temperature control.

[0026] An environmentally friendly soundproof composite material as described above, wherein the interior of the bio-based polyester fiber has a primary pre-network and a secondary pre-network structure of a honeycomb structure;

[0027] Assuming the porosity of the network unit in the pre-network structure is P, then:

[0028] P=1-\frac{V_{material}}{V_{total}}

[0029] Wherein, V_{material}: the volume of the material in the network structure; V_{total}: ​​the total volume of the network structure, including the material and pores; the porosity P is used to describe the proportion of voids in the network structure, reflecting the void situation inside the fiber;

[0030] Assuming the network density is rho_n, then:

[0031] rho_n=\frac{N}{A}

[0032] Among them, rho_n: network density, which means the number of network units per unit area; N: the number of network units; A: the area of ​​the investigated area; the network density rho_n reflects the density of the network units and has an impact on the mechanical properties and sound absorption properties of the fiber;

[0033] Assuming the network connectivity coefficient is C, then:

[0034] C=\frac{N_c}{N_t}

[0035] Wherein, C: network connectivity coefficient; N_c: the number of interconnected network units; N_t: the total number of network units; the network connectivity coefficient C is used to evaluate the degree of connectivity between units in the network structure, which has an important influence on the air permeability and sound wave propagation characteristics of the material;

[0036] Assuming the average pore size of the pre-network structure is D_{pore}, then:

[0037] D_{pore}=\frac{\sum_{i=1}^{n}d_i}{n}

[0038] Among them, D_{pore}: the average pore size of the pre-network structure; d_i: the diameter of the i-th pore; n: the number of pores; the average pore size D_{pore} reflects the size of the pores in the pre-network structure, which has a direct impact on the sound absorption performance and air permeability of the material.

[0039] In the environmentally friendly soundproof composite material as described above, the surface of the metal plate is treated to form a microscopic three-dimensional corrugated structure; the surface of the nanosilicate carries positive and negative charges, and is tightly combined with other components in the composite material through electrostatic action to form a stable three-dimensional network structure; the conductive filler has linearly arranged conductive channels, and / or forms a three-dimensional conductive network in the composite material through surface treatment, thereby effectively improving the conductive properties and antistatic ability of the material.

[0040] The second invention of the present invention provides a production process of an environmentally friendly sound-proof composite material, comprising the following steps:

[0041] S1: Select biodegradable PE polymer material as the basis, use an ultrasonic processor to pre-treat the PE polymer material to partially break its molecular chain and increase active points, and then pre-mix the PE polymer material with the plasticizer in a low-speed mixer to allow the plasticizer to evenly penetrate into the PE;

[0042] S2: adding a crosslinking agent, using a bio-based crosslinking agent, a plant extract containing multiple active functional groups, and continuing to mix and react with the active points in the PE polymer material at a temperature of 60 to 80°C for 2 to 4 hours to form a preliminary crosslinking network;

[0043] S3: Under the condition of a pressure of 100 to 300 MPa, the conductive filler is uniformly dispersed in the PE polymer material by a high-pressure homogenizer to obtain a PE polymer material base layer;

[0044] S4: On the PE polymer material base layer, a layer of bio-based polyester fiber mesh is bonded by hot-melt bonding technology at a temperature of 180-220° C. to enhance the strength and toughness of the composite material, and a layer of film containing phase change material microcapsules and nano-silicate is bonded on the bio-based polyester fiber mesh at a temperature of 80-120° C. for sound absorption and sound insulation to obtain a PE polymer composite material;

[0045] S5: Chemical etching or laser etching technology is used to form a microscopic three-dimensional corrugated structure on the surface of the metal sheet. The metal coil is leveled and high-frequency heated to 150-200°C, and then an adhesive is applied and the metal sheet and the PE polymer composite material are rolled and aligned under 5-15MPa conditions to make them close to the same surface for hot pressing and lamination for a duration of 10-30 seconds.

[0046] S6: After the hot pressing is completed, the cooling air conditioner is used for synchronous cooling to fully solidify the adhesive, and then the adhesive is rolled up or flattened according to the required size to obtain a silent composite material.

[0047] As the preferred technical solution:

[0048] The production process of an environmentally friendly soundproof composite material as described above also includes: using bio-based coatings to surface treat the composite materials to improve their wear resistance, corrosion resistance and anti-static properties, and using light curing technology and / or cold air rapid cooling to allow the coating to quickly cure in a short time, thereby reducing energy consumption and pollution.

[0049] As described above, in the production process of an environmentally friendly sound-proof composite material, in S1, a biodegradable PE polymer material is selected as the basis, and the PE polymer material is pretreated using an ultrasonic processor at a frequency of 20 to 40 kHz for 10 to 30 minutes to partially break its molecular chains and increase active points. The PE polymer material is then premixed with a plasticizer in a low-speed mixer, the speed is controlled at 50 to 100 rpm, and the mixing time is 30 to 60 minutes, so that the plasticizer can evenly penetrate into the PE.

[0050] As described above, a production process of an environmentally friendly sound-proof composite material introduces an n+1-level branch structure on the polymer chain of the PE polymer material to ensure that the length of each branch structure is 1 / 3 to 1 / 2 of the length of the main chain. Multiple cross-linking points are formed on the polymer chain through chemical cross-linking or radiation cross-linking to improve the strength and heat resistance of the material. The bio-based polyester fiber is pre-treated to form a stable honeycomb structure pre-network inside it.

[0051] Compared with the existing technology, the present invention uses biodegradable PE polymer materials as the basis, combined with a variety of environmentally friendly and high-performance material components such as bio-based polyester fibers, phase change material microcapsules, nano-silicates, etc. Through innovative production processes, such as ultrasonic pretreatment, the formation of a cross-linked network, high-pressure homogenization and dispersion, etc., the environmental protection, durability, vibration reduction and noise reduction performance, and multifunctionality of the composite material are effectively improved. This technical solution provides new ideas and methods for the research and development of environmentally friendly silent composite materials;

[0052] Beneficial effects and benefits:

[0053] Environmental protection: We use environmentally friendly materials such as biodegradable PE polymer materials and bio-based polyester fibers to reduce pollution to the environment. At the same time, we also focus on energy conservation and emission reduction during the production process, such as the use of bio-based coatings and light curing technology, which reduces energy consumption and pollution.

[0054] Excellent quiet performance: By introducing phase change material microcapsules, nanosilicates and specific metal sheet structures, the composite material has excellent quiet effect, which can effectively reduce noise transmission and improve the comfort of living and working environments.

[0055] High strength and durability: The polymer chain of PE polymer material introduces n+1 branching structure and multiple cross-linking points, which enhances the strength and heat resistance of the material. At the same time, the pretreatment of bio-based polyester fiber also forms a stable honeycomb structure pre-network inside it, further improving the mechanical properties of the composite material.

[0056] Versatility: This composite material not only has a silent function, but also has good corrosion resistance, aging resistance, temperature resistance and fire resistance. In addition, its surface is smooth and hard, and can meet food grade standards. It is widely used in drinking water tanks, fire water tanks, chemical storage tanks, underground pools, swimming pools, breeding pools, indoor and outdoor wall panels, door panels, desktop panels, roofs and other fields, and it is energy-saving, environmentally friendly and does not fade.

[0057] In summary, the present invention provides a high-performance, environmentally friendly and multifunctional sound-proof composite material and a production process thereof, which has broad application prospects and significant social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 It is a data line chart of the embodiments and comparative examples of the present invention;

[0059] Figure 2 It is a data bar chart of the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION

[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values ​​between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."

[0061] The present invention is further explained below in conjunction with specific examples. In the following examples, various processes and methods not described in detail are conventional methods known in the art. The materials, reagents, devices, instruments, equipment, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.

[0062] An environmentally friendly soundproof composite material comprises the following components in parts by weight: 10 to 20 parts of PE polymer material, 100 to 150 parts of metal plate, 10 to 15 parts of bio-based polyester fiber, 5 to 10 parts of phase change material microcapsules, 3 to 5 parts of nano silicate, 5 to 10 parts of conductive filler, 1 to 3 parts of crosslinking agent, 2 to 4 parts of plasticizer and 2 to 4 parts of adhesive.

[0063] In the embodiments mentioned below, polyethylene is selected as the PE polymer material, and the molecular weight of the PE polymer material is 100,000 to 300,000 Daltons. Under the conditions of 190°C / 2.16kg, the melt index is 1 to 10g / 10min; the metal plate is selected from one or more of aluminum plate, steel plate, and copper plate, the thickness of the metal plate is 0.1 to 0.5mm, and the surface roughness Ra value is less than 0.8μm; the bio-based polyester fiber is a bio-based polyester fiber made from corn starch, the fiber diameter of the bio-based polyester fiber is between 10 and 30μm, and the fiber length is 3 to 12mm; the phase change material microcapsule contains phase change material paraffin, the microcapsule diameter of the phase change material microcapsule is 5 to 50μm, and the phase change temperature range is 20 to 30°C; the conductive filler is selected from one or more of carbon black, carbon nanotubes, and graphene, the cross-linking agent is a silane cross-linking agent, the plasticizer is one of an epoxy plasticizer and a citrate plasticizer, and the adhesive is one or more of a plant-based adhesive, a water-based polyurethane adhesive, and a bio-based composite adhesive.

[0064] The polymer chain of the PE polymer material has n+1 branch structures, the length of each branch structure is 1 / 3 to 1 / 2 of the length of the main chain, and / or the polymer chain has multiple cross-linking points;

[0065] Assuming the ratio of the length of the branch structure to the length of the main chain is R_{branch}, then:

[0066] R_{branch}=\frac{L_{branch}}{L_{main}}

[0067] Among them, L_{branch} is the average length of the branch structure; L_{main} is the length of the main chain; it is used to ensure that the length of the branch structure is 1 / 3 to 1 / 2 of the length of the main chain;

[0068] Assuming the complexity of the branch structure is C_{branch}, then:

[0069] C_{branch}=\frac{N_{branches}}{N_{levels}}

[0070] Where, N_{branches}: the total number of branches; N_{levels}: the level of the branch structure; this complexity index evaluates the impact of the branch structure on material properties;

[0071] Assuming the density of crosslink points is D_{crosslink}, then:

[0072] D_{crosslink}=\frac{N_{crosslink}}{L_{chain}}

[0073] Wherein, N_{crosslink}: the number of crosslink points on the polymer chain; L_{chain}: the total length of the polymer chain, including the main chain and branch chains; the crosslink point density reflects the degree of crosslinking of the polymer chain;

[0074] Example:

[0075] A PE polymer material, whose main chain length (L_{main}) is set to the length of 300 carbon-carbon bonds. In order to meet the requirement that the length of the branch structure is 1 / 3 to 1 / 2 of the main chain length, the average length of the branch structure (L_{branch}) is designed to be 120 carbon-carbon bonds. In this way, the ratio of the length of the branch structure to the length of the main chain (R_{branch}) is 0.4, which meets the requirement of 1 / 3 to 1 / 2.

[0076] In this design, each branch structure is set to have 3 levels, that is, N_{levels}=3, and each level has 4 branches, so the total number of branches (N_{branches}) is 12. Therefore, the complexity of the branch structure (C_{branch}) is 4 (that is, 12 divided by 3).

[0077] In order to increase the stability and durability of the material, crosslinking points are introduced on the polymer chain. In this example, the total length of the polymer chain (L_{chain}), including the main chain and all branch chains, is set to the length of 1200 carbon-carbon bonds. On the polymer chain, we set 20 crosslinking points, so the density of crosslinking points (D_{crosslink}) is 0.0167 (i.e. 20 divided by 1200).

[0078] The shell of phase change material microcapsules undergoes reversible deformation when the temperature changes, presenting a tightly arranged linear structure at low temperatures and a loose network structure at high temperatures, thereby achieving more efficient temperature control.

[0079] The interior of the bio-based polyester fiber has a primary pre-network and a secondary pre-network structure of a honeycomb structure;

[0080] Assuming the porosity of the network unit in the pre-network structure is P, then:

[0081] P=1-\frac{V_{material}}{V_{total}}

[0082] Wherein, V_{material}: the volume of the material in the network structure; V_{total}: ​​the total volume of the network structure, including the material and pores; the porosity P is used to describe the proportion of voids in the network structure, reflecting the void situation inside the fiber;

[0083] Assuming the network density is rho_n, then:

[0084] rho_n=\frac{N}{A}

[0085] Among them, rho_n: network density, which means the number of network units per unit area; N: the number of network units; A: the area of ​​the investigated area; the network density rho_n reflects the density of the network units and has an impact on the mechanical properties and sound absorption properties of the fiber;

[0086] Assuming the network connectivity coefficient is C, then:

[0087] C=\frac{N_c}{N_t}

[0088] Wherein, C: network connectivity coefficient; N_c: the number of interconnected network units; N_t: the total number of network units; the network connectivity coefficient C is used to evaluate the degree of connectivity between units in the network structure, which has an important influence on the air permeability and sound wave propagation characteristics of the material;

[0089] Assuming the average pore size of the pre-network structure is D_{pore}, then:

[0090] D_{pore}=\frac{\sum_{i=1}^{n}d_i}{n}

[0091] Among them, D_{pore}: the average pore size of the pre-network structure; d_i: the diameter of the i-th pore; n: the number of pores; the average pore size D_{pore} reflects the size of the pores in the pre-network structure, which has a direct impact on the sound absorption performance and air permeability of the material.

[0092] Example:

[0093] A bio-based polyester fiber is designed with a specific honeycomb structure inside. This structure consists of a primary pre-network and a secondary pre-network, aiming to optimize the fiber's sound absorption performance and air permeability.

[0094] First, the porosity (P) of the network unit in the pre-network structure is set. By calculation, the volume of the material in the network structure (V_{material}) is 0.8 cubic centimeters, and the total volume of the network structure (V_{total}), including the material and the pores, is 1.6 cubic centimeters. According to the porosity formula, the porosity (P) is 0.5, which means that the voids in the network structure occupy half of the total volume.

[0095] Next, the network density (rho_n) is calculated. In the 1 square centimeter area under consideration, the number of network units (N) is 25. Therefore, the network density (rho_n) is 25 / square centimeter, reflecting the density of network units.

[0096] In order to evaluate the degree of connectivity between units in the network structure, the network connectivity coefficient (C) is calculated. In the designed structure, 20 network units are interconnected, and the total number of network units (N_t) is 25. According to the formula, the network connectivity coefficient (C) is 0.8, indicating that most network units are interconnected.

[0097] Finally, calculate the average pore size (D_{pore}) of the pre-network structure. Through measurement, we get the diameter data of 10 holes: 0.2 mm, 0.25 mm, 0.2 mm, 0.3 mm, 0.25 mm, 0.2 mm, 0.3 mm, 0.25 mm, 0.2 mm and 0.3 mm. According to the formula of average pore size, the average pore size (D_{pore}) is 0.25 mm.

[0098] Through the above design, a bio-based polyester fiber with a specific honeycomb structure was obtained. The porosity, network density, network connectivity coefficient and average pore size of this fiber have been accurately calculated and designed to meet specific sound absorption and air permeability requirements. Such a design helps to improve the application effect of the fiber in environmentally friendly silent composite materials.

[0099] The surface of the metal sheet is treated to form a microscopic three-dimensional corrugated structure; the surface of the nanosilicate carries positive and negative charges, and is tightly combined with other components in the composite material through electrostatic action to form a stable three-dimensional network structure; the conductive filler has linearly arranged conductive channels, and / or forms a three-dimensional conductive network in the composite material through surface treatment, thereby effectively improving the conductive properties and antistatic ability of the material.

[0100] Example:

[0101] Sheet metal surface treatment

[0102] An aluminum alloy plate was selected and a microscopic three-dimensional corrugated structure was formed on its surface by chemical etching. The specific operation is: immerse the aluminum alloy plate in a mixed solution containing 10% hydrochloric acid and 5% hydrofluoric acid, control the etching time to 15 minutes, and the temperature to 25°C. After etching, rinse thoroughly with deionized water and dry. Through scanning electron microscope observation, it can be clearly seen that a three-dimensional corrugated structure with an average wave height of 5 microns and a wavelength of 20 microns is formed on the surface of the plate.

[0103] Electrostatic bonding of nanosilicates

[0104] Nano silicate powder is selected, and its surface is specially treated with positive and negative charges. Nano silicate is mixed with PE matrix and other additives, and evenly mixed by high-speed mixer. Nano silicate is closely combined with other components in the composite material due to electrostatic effect, forming a stable three-dimensional network structure. Through transmission electron microscopy, it can be clearly seen that nano silicate is evenly distributed in the composite material and is closely combined with the surrounding components.

[0105] Conductive network construction of conductive fillers

[0106] Carbon nanotubes are selected as conductive fillers, which have excellent conductive properties. First, the carbon nanotubes are surface treated so that their surfaces carry carboxyl functional groups to increase their compatibility with the composite material. Then, the treated carbon nanotubes are mixed with the PE matrix and other additives to prepare the composite material by melt blending. During the melt blending process, the carbon nanotubes form a three-dimensional conductive network in the composite material. The resistivity of the composite material was measured by the four-probe method, and it was found that its resistivity was significantly reduced, indicating that the conductive network effectively improves the conductive properties of the material. At the same time, through antistatic testing, it was found that the antistatic ability of the composite material has also been significantly improved.

[0107] In summary, through the method of this embodiment, we have successfully achieved the three-dimensional corrugated structure treatment of the metal sheet surface, the electrostatic bonding of nanosilicates, and the conductive network construction of conductive fillers, thereby effectively improving the conductive properties and antistatic ability of the environmentally friendly silent composite material.

[0108] Embodiment 1

[0109] An environmentally friendly soundproof composite material comprises the following components in parts by weight: 10 parts of PE polymer material, 100 parts of metal plate, 10 parts of bio-based polyester fiber, 5 parts of phase change material microcapsules, 3 parts of nano-silicate, 5 parts of conductive filler, 1 part of cross-linking agent, 2 parts of plasticizer, and 2 parts of adhesive.

[0110] The embodiment also provides a production process of an environmentally friendly sound-proof composite material, comprising the following steps:

[0111] S1: Select biodegradable PE polymer material as the basis, use an ultrasonic processor to pre-treat the PE polymer material at a frequency of 20KHz for 10 minutes to partially break its molecular chain and increase active points, and then pre-mix the PE polymer material with the plasticizer in a low-speed mixer at a speed of 50rpm for 30 minutes to allow the plasticizer to evenly penetrate into the PE;

[0112] S2: adding a crosslinking agent, using a bio-based crosslinking agent, a plant extract containing multiple active functional groups, and continuing to mix and react with the active points in the PE polymer material at a temperature of 60°C for 2 hours to form a preliminary crosslinking network;

[0113] S3: Under the condition of a pressure of 100 MPa, the conductive filler is uniformly dispersed in the PE polymer material by a high-pressure homogenizer to obtain a PE polymer material base layer;

[0114] S4: On the PE polymer material base layer, a layer of bio-based polyester fiber mesh is bonded by hot-melt bonding technology at a temperature of 180°C to enhance the strength and toughness of the composite material, and a layer of film containing phase change material microcapsules and nano-silicate is bonded on the bio-based polyester fiber mesh at 80°C for sound absorption and sound insulation to obtain a PE polymer composite material;

[0115] S5: Chemical etching or laser etching technology is used to form a microscopic three-dimensional corrugated structure on the surface of the metal sheet. The metal coil is leveled and high-frequency heated to 150°C, and then an adhesive is applied and the metal sheet and the PE polymer composite material are rolled and aligned under 5MPa conditions to make them close to the same surface for hot pressing and lamination for 10 seconds;

[0116] S6: When the hot pressing is completed, the cooling air conditioner is used for synchronous cooling to fully solidify the adhesive, and then the adhesive is rolled up or flattened according to the required size to obtain a silent composite material;

[0117] S7: Use bio-based coatings to treat the surface of composite materials to improve their wear resistance, corrosion resistance and anti-static properties. Through light curing technology and / or rapid cooling with cold air, the coating can be quickly cured in a short time, reducing energy consumption and pollution.

[0118] Among them, an n+1 level branch structure is introduced on the polymer chain of PE polymer material to ensure that the length of each branch structure is 1 / 3 of the length of the main chain. Through chemical cross-linking or radiation cross-linking, multiple cross-linking points are formed on the polymer chain to improve the strength and heat resistance of the material. The bio-based polyester fiber is pre-treated to form a stable honeycomb structure pre-network inside it.

[0119] Embodiment 2

[0120] An environmentally friendly soundproof composite material comprises the following components in parts by weight: 15 parts of PE polymer material, 120 parts of metal sheet, 12 parts of bio-based polyester fiber, 7 parts of phase change material microcapsules, 4 parts of nano-silicate, 6 parts of conductive filler, 2 parts of cross-linking agent, 3 parts of plasticizer and 3 parts of adhesive.

[0121] The embodiment also provides a production process of an environmentally friendly sound-proof composite material, comprising the following steps:

[0122] S1: Biodegradable PE polymer material is selected as the basis, and the PE polymer material is pretreated with an ultrasonic processor at a frequency of 25KHz for 15 minutes to partially break its molecular chain and increase the active points. Then the PE polymer material is premixed with the plasticizer in a low-speed mixer at a speed of 60rpm for 35 minutes to allow the plasticizer to evenly penetrate into the PE.

[0123] S2: adding a crosslinking agent, using a bio-based crosslinking agent, a plant extract containing multiple active functional groups, and continuing to mix and react with the active points in the PE polymer material at a temperature of 65°C for 3 hours to form a preliminary crosslinking network;

[0124] S3: Under a pressure of 150 MPa, the conductive filler is uniformly dispersed in the PE polymer material by a high-pressure homogenizer to obtain a PE polymer material base layer;

[0125] S4: On the PE polymer material base layer, a layer of bio-based polyester fiber mesh is bonded by hot-melt bonding technology at a temperature of 190°C to enhance the strength and toughness of the composite material, and a layer of film containing phase change material microcapsules and nano-silicate is bonded on the bio-based polyester fiber mesh at 90°C for sound absorption and sound insulation to obtain a PE polymer composite material;

[0126] S5: Chemical etching or laser etching technology is used to form a microscopic three-dimensional corrugated structure on the surface of the metal sheet. The metal coil is leveled and high-frequency heated to 160°C, and then the adhesive is applied and the metal sheet and the PE polymer composite material are rolled and aligned under 8MPa conditions to make them close to the same surface for hot pressing and lamination for 15 seconds;

[0127] S6: When the hot pressing is completed, the cooling air conditioner is used for synchronous cooling to fully solidify the adhesive, and then the adhesive is rolled up or flattened according to the required size to obtain a silent composite material;

[0128] S7: Use bio-based coatings to treat the surface of composite materials to improve their wear resistance, corrosion resistance and anti-static properties. Through light curing technology and / or rapid cooling with cold air, the coating can be quickly cured in a short time, reducing energy consumption and pollution.

[0129] Among them, an n+1 level branch structure is introduced on the polymer chain of PE polymer material to ensure that the length of each branch structure is 1 / 3 of the length of the main chain. Through chemical cross-linking or radiation cross-linking, multiple cross-linking points are formed on the polymer chain to improve the strength and heat resistance of the material. The bio-based polyester fiber is pre-treated to form a stable honeycomb structure pre-network inside it.

[0130] Embodiment 3

[0131] An environmentally friendly soundproof composite material comprises the following components in parts by weight: 18 parts of PE polymer material, 140 parts of metal sheet, 13 parts of bio-based polyester fiber, 8 parts of phase change material microcapsules, 4 parts of nano-silicate, 8 parts of conductive filler, 2 parts of cross-linking agent, 3 parts of plasticizer, and 3 parts of adhesive.

[0132] The embodiment also provides a production process of an environmentally friendly sound-proof composite material, comprising the following steps:

[0133] S1: Biodegradable PE polymer material is selected as the basis, and the PE polymer material is pretreated with an ultrasonic processor at a frequency of 30KHz for 20 minutes to partially break its molecular chain and increase the active points. Then the PE polymer material is premixed with the plasticizer in a low-speed mixer at a speed of 80rpm for 50 minutes to make the plasticizer evenly penetrate into the PE.

[0134] S2: adding a crosslinking agent, using a bio-based crosslinking agent, a plant extract containing multiple active functional groups, and continuing to mix and react with the active points in the PE polymer material at a temperature of 70°C for 3 hours to form a preliminary crosslinking network;

[0135] S3: Under the condition of a pressure of 200 MPa, the conductive filler is uniformly dispersed in the PE polymer material by a high-pressure homogenizer to obtain a PE polymer material base layer;

[0136] S4: A layer of bio-based polyester fiber mesh is bonded to the PE polymer material base layer by hot-melt bonding technology at a temperature of 210°C to enhance the strength and toughness of the composite material, and a layer of film containing phase change material microcapsules and nano-silicate is bonded to the bio-based polyester fiber mesh at 100°C for sound absorption and sound insulation to obtain a PE polymer composite material;

[0137] S5: Chemical etching or laser etching technology is used to form a microscopic three-dimensional corrugated structure on the surface of the metal sheet. The metal coil is leveled and high-frequency heated to 180°C, and then the adhesive is applied and the metal sheet and the PE polymer composite material are rolled and aligned under 12MPa conditions to make them close to the same surface for hot pressing and lamination for 20 seconds;

[0138] S6: When the hot pressing is completed, the cooling air conditioner is used for synchronous cooling to fully solidify the adhesive, and then the adhesive is rolled up or flattened according to the required size to obtain a silent composite material;

[0139] S7: Use bio-based coatings to treat the surface of composite materials to improve their wear resistance, corrosion resistance and anti-static properties. Through light curing technology and / or rapid cooling with cold air, the coating can be quickly cured in a short time, reducing energy consumption and pollution.

[0140] Among them, an n+1 level branch structure is introduced on the polymer chain of PE polymer material to ensure that the length of each branch structure is 1 / 2 of the length of the main chain. Through chemical cross-linking or radiation cross-linking, multiple cross-linking points are formed on the polymer chain to improve the strength and heat resistance of the material. The bio-based polyester fiber is pre-treated to form a stable honeycomb structure pre-network inside it.

[0141] Embodiment 4

[0142] An environmentally friendly soundproof composite material comprises the following components in parts by weight: 2 parts of PE polymer material, 150 parts of metal sheet, 15 parts of bio-based polyester fiber, 10 parts of phase change material microcapsules, 5 parts of nano-silicate, 10 parts of conductive filler, 3 parts of cross-linking agent, 4 parts of plasticizer and 4 parts of adhesive.

[0143] The embodiment also provides a production process of an environmentally friendly sound-proof composite material, comprising the following steps:

[0144] S1: Biodegradable PE polymer material is selected as the basis, and the PE polymer material is pretreated with an ultrasonic processor at a frequency of 40KHz for 30 minutes to partially break its molecular chain and increase the active points. Then the PE polymer material is premixed with the plasticizer in a low-speed mixer at a speed controlled at 100rpm for 60 minutes to allow the plasticizer to evenly penetrate into the PE.

[0145] S2: adding a crosslinking agent, using a bio-based crosslinking agent, a plant extract containing multiple active functional groups, and continuing to mix and react with the active points in the PE polymer material at a temperature of 80°C for 4 hours to form a preliminary crosslinking network;

[0146] S3: Under the condition of a pressure of 300 MPa, the conductive filler is uniformly dispersed in the PE polymer material by a high-pressure homogenizer to obtain a PE polymer material base layer;

[0147] S4: On the PE polymer material base layer, a layer of bio-based polyester fiber mesh is bonded by hot-melt bonding technology at a temperature of 220°C to enhance the strength and toughness of the composite material, and a layer of film containing phase change material microcapsules and nano-silicate is bonded on the bio-based polyester fiber mesh at 120°C for sound absorption and sound insulation to obtain a PE polymer composite material;

[0148] S5: Chemical etching or laser etching technology is used to form a microscopic three-dimensional corrugated structure on the surface of the metal sheet. The metal coil is leveled and high-frequency heated to 200°C, and then an adhesive is applied and the metal sheet and the PE polymer composite material are rolled and aligned under 15MPa conditions to make them close to the same surface for hot pressing and lamination for 30 seconds;

[0149] S6: When the hot pressing is completed, the cooling air conditioner is used for synchronous cooling to fully solidify the adhesive, and then the adhesive is rolled up or flattened according to the required size to obtain a silent composite material;

[0150] S7: Use bio-based coatings to treat the surface of composite materials to improve their wear resistance, corrosion resistance and anti-static properties. Through light curing technology and / or rapid cooling with cold air, the coating can be quickly cured in a short time, reducing energy consumption and pollution.

[0151] Among them, an n+1 level branch structure is introduced on the polymer chain of PE polymer material to ensure that the length of each branch structure is 1 / 2 of the length of the main chain. Through chemical cross-linking or radiation cross-linking, multiple cross-linking points are formed on the polymer chain to improve the strength and heat resistance of the material. The bio-based polyester fiber is pre-treated to form a stable honeycomb structure pre-network inside it.

[0152] Comparative Example 1

[0153] A production process of an environmentally friendly sound-proof composite material is basically the same as that of the fourth embodiment, except that:

[0154] The use of phase change material microcapsules and nano-silicate components is omitted.

[0155] Comparative Example 2

[0156] A production process of an environmentally friendly sound-proof composite material is basically the same as that of the fourth embodiment, except that:

[0157] The use of conductive filler as a component in the production process is eliminated.

[0158] Comparative Example 3

[0159] A production process of an environmentally friendly sound-proof composite material is basically the same as that of the fourth embodiment, except that:

[0160] The use of bio-based polyester fiber as a component in the production process is omitted.

[0161] Comparative Example 4

[0162] A production process of an environmentally friendly sound-proof composite material is basically the same as that of the fourth embodiment, except that:

[0163] The limited treatment of the n+1 level branching structure of the PE polymer material was removed, and only ordinary PE polymer material was used without the honeycomb structure pre-network treatment of the bio-based polyester fiber.

[0164] The sound-proof composite materials prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 were tested, and the testing was carried out according to the following standards:

[0165] GB / T 5455-2014 Textiles - Flammability Test - Vertical Method - Used to test the flame retardant properties of composite materials.

[0166] GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General" - used to test the tensile properties of composite materials.

[0167] GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test" - used to test the impact strength of composite materials.

[0168] GB / T 1904.1-2008 "Rigid plastics drop weight impact test method Part 1: General" - Another method for evaluating the impact resistance of materials.

[0169] GB / T 2423.17-2008 "Environmental testing for electrical and electronic products Part 2: Test method Test Ka: Salt spray" - Tests the corrosion resistance of composite materials in a salt spray environment.

[0170] GB / T 16406-1996 "Acoustics - Determination of the sound power level of a noise source by the sound pressure method - A simple method using an envelope measuring surface above a reflecting surface" - Testing the sound insulation performance of composite materials.

[0171] Specific detection method:

[0172] Flame retardant performance: Carry out vertical combustion test according to GB / T 5455 to observe the burning speed, burning time and residue after burning of the material.

[0173] Tensile properties and impact strength: standard specimens were prepared according to GB / T 1040.1 and GB / T 1043.1, and then tested using a tensile testing machine and an impact testing machine.

[0174] Corrosion resistance: Carry out salt spray test in accordance with GB / T 2423.17 to observe the corrosion of materials in salt spray environment.

[0175] Sound insulation performance: The sound insulation effect of composite materials is tested in a standard acoustic environment according to GB / T 16406.

[0176] The results are shown in Table 1:

[0177] Table 1

[0178]

[0179] Through the above Table 1, it can be directly obtained that the flame retardant properties of all embodiments are V-0, which is the highest flame retardant grade. This shows that all embodiments have reached very high standards in terms of flame retardancy. In tensile strength (MPa), the tensile strength of Example 1 is 33MPa; the tensile strength of Example 2 is 34MPa; the tensile strength of Example 3 is 34MPa; the tensile strength of Example 4 is 35MPa; the values ​​of tensile strength are slightly different between the embodiments, but are generally at a high level. From Example 1 to Example 4, the tensile strength shows a gradually increasing trend, and Example 4 has the highest tensile strength. In impact strength, the impact strength of Example 1 is 14kJ / m 2 The impact strength of Example 2 is 15 kJ / m 2 The impact strength of Example 3 is 14 kJ / m 2 The impact strength of Example 4 is 15 kJ / m 2 ; The values ​​of impact strength are the same between Example 1 and Example 3, and the same between Example 2 and Example 4. Overall, the impact strength of Example 2 and Example 4 is slightly higher than that of Example 1 and Example 3. The corrosion resistance of all embodiments is "no change", which shows that all embodiments excel in corrosion resistance. The values ​​of sound insulation performance vary between the embodiments, and the sound insulation performance gradually improves from Example 1 to Example 4. Example 4 has the highest sound insulation performance. It can be seen from the data that Example 4 shows the best performance in tensile strength, impact strength and sound insulation performance. This is due to the optimization of the component ratio or production process in Example 4. At the same time, all embodiments have reached high standards in flame retardancy and corrosion resistance.

[0180] Reference Figure 1-2 In Example 4 and Comparative Example 1 where other conditions are the same, Comparative Example 1 omits the use of phase change material microcapsules and nanosilicate components. After testing, the flame retardant performance of the final sound-proof composite material obtained in Example 4 is better than that in Comparative Example 1, reaching the highest flame retardant grade V-0; the tensile strength of Example 4 is significantly higher than that of Comparative Example 1, indicating that the material of Example 4 has stronger structural strength; the impact strength of Example 4 is significantly higher than that of Comparative Example 1, showing better toughness and impact resistance; Example 4 performs better in corrosion resistance, and no corrosion occurs; the sound insulation performance of Example 4 is significantly better than that of Comparative Example 1, indicating that it is more effective in reducing sound propagation.

[0181] In Comparative Example 2, the conductive filler component was removed from the production process. After testing, the final soundproof composite material showed that Comparative Example 2 and Example 4 had the same flame retardant properties, both reaching the highest level; the tensile strength of Example 4 was slightly higher than that of Comparative Example 2, but the difference between the two was not large; the impact strength of Example 4 was slightly higher than that of Comparative Example 2, showing better impact resistance; Comparative Example 2 and Example 4 had the same corrosion resistance, both without corrosion; the sound insulation performance of Example 4 was better than that of Comparative Example 2, and could better isolate sound.

[0182] Comparative Example 3 omits the use of the bio-based polyester fiber component in the production process. After testing, the final sound-proof composite material has the same flame retardant properties as Example 4, both reaching the highest level; the tensile strength of Example 4 is significantly higher than that of Comparative Example 3, indicating that its material structure is stronger; the impact strength of Example 4 is much higher than that of Comparative Example 3, indicating that its impact resistance is stronger; both perform well in corrosion resistance, and no corrosion occurs; the sound insulation performance of Example 4 is significantly better than that of Comparative Example 3, and can more effectively isolate noise.

[0183] In Comparative Example 4, the limiting treatment of the n+1 branch structure of the PE polymer material was removed, and only ordinary PE polymer material was used without performing the honeycomb structure pre-network treatment of the bio-based polyester fiber. After testing, the final sound-proof composite material of Example 4 had better flame retardant properties than Comparative Example 4; the tensile strength of Example 4 was much higher than that of Comparative Example 4, showing stronger structural stability; the impact strength of Example 4 was significantly higher than that of Comparative Example 4, and had stronger impact resistance; Example 4 performed better in corrosion resistance, and no corrosion occurred; the sound insulation performance of Example 4 was significantly better than that of Comparative Example 4, and had better sound insulation effect.

[0184] The present invention is mainly composed of PE polymer material, metal sheet, bio-based polyester fiber, phase change material microcapsule, nano silicate, conductive filler, etc. Among them, the PE polymer material has a specific branch and cross-linking structure, the surface of the metal sheet is processed to form a three-dimensional corrugated structure, the interior of the bio-based polyester fiber is designed to be a honeycomb structure, the phase change material microcapsule can change the structure when the temperature changes to adjust the temperature, the nano silicate is closely combined with the composite material through electrostatic action, and the conductive filler forms a three-dimensional conductive network to improve the conductivity and antistatic ability.

[0185] The use of environmentally friendly materials such as bio-based polyester fibers and plant-based adhesives reduces the impact on the environment and meets the requirements of green manufacturing and sustainable development; through carefully designed components and structures, such as bio-based polyester fibers with honeycomb structures and PE polymer materials with specific structures, the composite material has excellent sound insulation effect and effectively reduces noise transmission; phase change material microcapsules can change their structure when the temperature changes, thereby achieving efficient temperature regulation and improving the stability and service life of the material; the addition of nano-silicates is closely combined with the composite material through electrostatic action, enhancing the stability and mechanical properties of the material; the addition of conductive fillers, especially treated carbon nanotubes, forms a three-dimensional conductive network, which significantly improves the conductive properties and antistatic ability of the material, and increases the safety and reliability of the material; the three-dimensional corrugated structure on the surface of the metal sheet not only enhances the bonding force with other components, but also interferes with the propagation of sound waves, further improving the sound insulation effect.

[0186] The use of biodegradable PE polymer materials and bio-based cross-linking agents, adhesives, etc. reduces the impact on the environment and improves the sustainability of the materials; by introducing specific branch structures and cross-linking points on the polymer chain, the strength and heat resistance of the materials are improved. At the same time, the pretreatment of bio-based polyester fibers forms a stable honeycomb structure pre-network inside it, further enhancing the strength and toughness of the composite material; the film layer design containing phase change material microcapsules and nano-silicates gives the composite material excellent sound absorption and sound insulation properties; the uniform dispersion of conductive fillers improves the conductivity of the composite material and helps prevent static electricity accumulation; by optimizing the conditions and time of each production step, such as mixing time, reaction temperature, pressure, etc., the high efficiency of production and the consistency of material properties are ensured; the use of bio-based coatings for surface treatment and rapid curing through photocuring technology not only improves the wear resistance and corrosion resistance of the composite material, but also reduces energy consumption and pollution during the production process;

[0187] In summary, the present invention achieves comprehensive improvement of the environmental protection, performance, sound insulation effect, conductivity, anti-static ability, production efficiency and durability of the silent composite material through innovative production technology and selection of environmentally friendly materials.

[0188] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An environmentally friendly sound-proof composite material, characterized in that: The invention comprises the following components in parts by weight: 10 to 20 parts of PE polymer material, 100 to 150 parts of metal sheet, 10 to 15 parts of bio-based polyester fiber, 5 to 10 parts of phase change material microcapsules, 3 to 5 parts of nano-silicate, 5 to 10 parts of conductive filler, 1 to 3 parts of cross-linking agent, 2 to 4 parts of plasticizer, and 2 to 4 parts of adhesive; The production process of the environmentally friendly sound-proof composite material comprises the following steps: S1: Select biodegradable PE polymer material as the basis, use an ultrasonic processor to pre-treat the PE polymer material to partially break its molecular chain and increase active points, and then pre-mix the PE polymer material with the plasticizer in a low-speed mixer to allow the plasticizer to evenly penetrate into the PE; S2: adding a crosslinking agent, using a bio-based crosslinking agent, a plant extract containing multiple active functional groups, and continuing to mix and react with the active points in the PE polymer material at a temperature of 60 to 80°C for 2 to 4 hours to form a preliminary crosslinking network; S3: Under the condition of a pressure of 100 to 300 MPa, the conductive filler is uniformly dispersed in the PE polymer material by a high-pressure homogenizer to obtain a PE polymer material base layer; S4: On the PE polymer material base layer, a layer of bio-based polyester fiber mesh is bonded by hot-melt bonding technology at a temperature of 180-220° C. to enhance the strength and toughness of the composite material, and a layer of film containing phase change material microcapsules and nano-silicate is bonded on the bio-based polyester fiber mesh at a temperature of 80-120° C. for sound absorption and sound insulation to obtain a PE polymer composite material; S5: Chemical etching or laser etching technology is used to form a microscopic three-dimensional corrugated structure on the surface of the metal sheet. The metal coil is leveled and high-frequency heated to 150-200°C, and then an adhesive is applied and the metal sheet and the PE polymer composite material are rolled and aligned under 5-15MPa conditions to make them close to the same surface for hot pressing and lamination for a duration of 10-30 seconds. S6: When the hot pressing is completed, the cooling air conditioner is used for synchronous cooling to fully solidify the adhesive, and then the adhesive is rolled up or flattened according to the required size to obtain a silent composite material; The PE polymer material has n+1-level branch structures on the polymer chain, the length of each branch structure is 1 / 3 to 1 / 2 of the length of the main chain, and / or the polymer chain has multiple cross-linking points; Assuming the ratio of the length of the branch structure to the length of the main chain is R_{branch}, then: R_{branch}=\frac{L_{branch}}{L_{main}} Among them, L_{branch} is the average length of the branch structure; L_{main} is the length of the main chain; it is used to ensure that the length of the branch structure is 1 / 3 to 1 / 2 of the length of the main chain; Assuming the complexity of the branch structure is C_{branch}, then: C_{branch}=\frac{N_{branches}}{N_{levels}} Where, N_{branches}: the total number of branches; N_{levels}: the level of the branch structure; this complexity index evaluates the impact of the branch structure on material properties; Assuming the density of crosslink points is D_{crosslink}, then: D_{crosslink}=\frac{N_{crosslink}}{L_{chain}} Wherein, N_{crosslink}: the number of crosslink points on the polymer chain; L_{chain}: the total length of the polymer chain, including the main chain and branch chains; the crosslink point density reflects the degree of crosslinking of the polymer chain; The shell of the phase change material microcapsule undergoes reversible deformation when the temperature changes, presenting a tightly arranged linear structure at low temperatures and changing into a loose network structure at high temperatures, thereby achieving more efficient temperature control.

2. The environmentally friendly sound-proof composite material according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 15 parts of PE polymer material, 120 parts of metal sheet, 12 parts of bio-based polyester fiber, 6 parts of phase change material microcapsule, 4 parts of nano silicate, 7 parts of conductive filler, 2 parts of cross-linking agent, 3 parts of plasticizer and 3 parts of adhesive.

3. An environmentally friendly sound-proof composite material according to claim 1 or 2, characterized in that: The PE polymer material is polyethylene, the molecular weight of the PE polymer material is 100,000 to 300,000 Daltons, and the melt index is 1 to 10 g / 10 min at 190° C. / 2.16 kg. The metal plate is one or more of aluminum plate, steel plate, and copper plate, the thickness of the metal plate is 0.1 to 0.5 mm, and the surface roughness Ra value is less than 0.8 μm. The bio-based polyester fiber is a bio-based polyester fiber made from corn starch, and the fiber diameter of the bio-based polyester fiber is 10 to 30μm, and the fiber length is 3-12mm; the phase change material microcapsule contains phase change material paraffin, the microcapsule diameter of the phase change material microcapsule is 5-50μm, and the phase change temperature range is 20-30℃; the conductive filler is one or more of carbon black, carbon nanotubes, and graphene, the cross-linking agent is a silane cross-linking agent, the plasticizer is one of an epoxy plasticizer and a citrate plasticizer, and the adhesive is one or more of a plant-based adhesive, a water-based polyurethane adhesive, and a bio-based composite adhesive.

4. The environmentally friendly sound-proof composite material according to claim 1, characterized in that: The bio-based polyester fiber has a primary pre-network and a secondary pre-network structure of a honeycomb structure inside; Assuming the porosity of the network unit in the pre-network structure is P, then: P=1-\frac{V_{material}}{V_{total}} Wherein, V_{material}: the volume of the material in the network structure; V_{total}: ​​the total volume of the network structure, including the material and pores; the porosity P is used to describe the proportion of voids in the network structure, reflecting the void situation inside the fiber; Assuming the network density is rho_n, then: rho_n=\frac{N}{A} Among them, rho_n: network density, which means the number of network units per unit area; N: the number of network units; A: the area of ​​the investigated area; the network density rho_n reflects the density of the network units and has an impact on the mechanical properties and sound absorption properties of the fiber; Assuming the network connectivity coefficient is C, then: C = \frac{N_c}{N_t} Wherein, C: network connectivity coefficient; N_c: the number of interconnected network units; N_t: the total number of network units; the network connectivity coefficient C is used to evaluate the degree of connectivity between units in the network structure, which has an important influence on the air permeability and sound wave propagation characteristics of the material; Assuming the average pore size of the pre-network structure is D_{pore}, then: D_{pore}=\frac{\sum_{i=1}^{n}d_i}{n} Among them, D_{pore}: the average pore size of the pre-network structure; d_i: the diameter of the i-th pore; n: the number of pores; the average pore size D_{pore} reflects the size of the pores in the pre-network structure, which has a direct impact on the sound absorption performance and air permeability of the material.

5. The environmentally friendly sound-proof composite material according to claim 1, characterized in that: The surface of the metal sheet is processed to form a microscopic three-dimensional corrugated structure; The surface of the nano-silicate has positive and negative charges, and is tightly combined with other components in the composite material through electrostatic action to form a stable three-dimensional network structure; The conductive filler has linearly arranged conductive channels and / or forms a three-dimensional conductive network in the composite material through surface treatment, thereby effectively improving the conductive performance and antistatic ability of the material.

6. The environmentally friendly soundproof composite material according to claim 1, characterized in that Also includes: Use bio-based coatings to treat the surface of composite materials to improve their wear resistance, corrosion resistance and anti-static properties. Through light curing technology and / or rapid cooling with cold air, the coating can be quickly cured in a short time, reducing energy consumption and pollution.

7. The environmentally friendly sound-proof composite material according to claim 1, characterized in that: In the S1, a biodegradable PE polymer material is selected as a basis, and the PE polymer material is pretreated by an ultrasonic processor at a frequency of 20 to 40 kHz for 10 to 30 minutes to partially break its molecular chains and increase active points. The PE polymer material is then premixed with a plasticizer in a low-speed mixer at a speed controlled at 50 to 100 rpm for 30 to 60 minutes to allow the plasticizer to evenly penetrate into the PE.

8. The environmentally friendly sound-proof composite material according to claim 1, characterized in that: An n+1 level branching structure is introduced into the polymer chain of PE polymer material to ensure that the length of each branch structure is 1 / 3 to 1 / 2 of the length of the main chain. Multiple cross-linking points are formed on the polymer chain through chemical cross-linking or radiation cross-linking to improve the strength and heat resistance of the material. The bio-based polyester fiber is pre-treated to form a stable honeycomb structure pre-network inside it.

Citation Information

Patent Citations

  • Protective film for external wall insulation material

    CN110629894A

  • Wear-resistant, noise-reducing and thin-walled polypropylene composite material and preparation method thereof

    CN111117075A

  • Bio-based polyester fiber as well as preparation method and antibacterial property testing method thereof

    CN114318576A